Polarization Imaging of Liquid Crystal Polymer Using Terahertz Difference-Frequency Generation Source - Atsushi Nakanishi (MDPI AG, 2021)
We performed the polarization imaging of a liquid crystal polymer with a terahertz difference-frequency generation (THz DFG) source. The DFG source is an easy-to-operate and practical THz source. Liquid crystal polymers (LCPs) are suitable for applications such as fuel cell components, aircraft parts, and next-generation wireless communication materials. Accordingly, the demand for evaluating the orientation of liquid crystals, which affects the properties of the polymers, is set to increase. Since LCPs exhibit birefringence in the THz range due to the orientation of the liquid crystal molecules, we can determine the alignment of the molecules from the direction of the optical axis.